Land Art. - Tiberghien, G.A (Paris : Carré, 1995)
Andre, Carl ; Arnatt, Keith ; Bayer, Herbert ; Borglum, Gutzon ; Brancusi, Constantin ; Christo ; Dibbets, Jan ; Flanagan, Barry ; Haacke, Hans ; Harrison, Newton ; Heizer, Michael ; Holt, Nancy ; Huebler, Douglas ; Hutchinson, Peter ; Johns, Jasper ; Judd, Donald ; Kaltenbach, Stephan ; LeWitt, Sol ; Long, Richard ; de Maria, Walter ; Matta-Clark, Gordon ; Morris, Robert ; Oldenburg, Claes ; Oppenheim, Dennis ; Ross, Charles ; Schum, Gerry ; Smith, Tony ; Smithson, Robert ; Sonfist, Alan ; Turrell, James
boek